The Role of Sri Baduga Maharaja in the Spread of Islam in The Sunda Region - Supendi, Usman; Nurcahya, Yan; Maulana, Ahmad Sobri; Nugraha, Patra Sentosa; Syakira, Mutiara Khansa; Salsabila, Marisa Jahra (INDO PUBLISHING, 2025)
Sri Baduga Maharaja (Prabu Siliwangi) was a great king of the Sunda Kingdom who ruled around 1482–1521 AD, and was known as a just, wise, and peace-loving leader. The data is then analyzed using qualitative data analysis techniques, starting with data reduction to filter relevant information from all sources. From this statement, it can be concluded that at that time there was a religious shift, with many Pajajaran people converting to Islam. Sri Baduga Maharaja did not directly spread Islam, but he played a role in creating peaceful and tolerant conditions that allowed Islam to spread well in the Sunda Kingdom. His open attitude towards religious differences made his reign one of the important periods in the early history of Islam in the Land of Sunda. reflecting how religion and culture are harmoniously intertwined. In this context, studying this collection of relics is an important means of understanding how Islam grew and took root in the cultural expressions of the Sundanese people.